2013
DOI: 10.5539/esr.v3n1p14
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Soil Liquefaction Potential

Abstract: Soil liquefaction is the source of several major damages during earthquakes on the material and human level. Several authors have studied the probability of liquefaction by in situ and laboratory tests and several models have been proposed to calculate the safety factor. But because of various uncertainties in performance function parameters, we adopted in this paper a reliability analysis that considers uncertainties of parameters and model uncertainties. We used the Monte Carlo simulation (MCS) to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The mean value of A was set to 2060, in line with the work conducted by Liu and Zhang 53 . A coefficient of variation (COV) of 0.2 is adopted for A in agreement with the COV values reported by Schevenels et al 57 and Ayad et al, 58 who also modeled G max as a random field. It is important to note that the mean effective normal stress ptrue′ ${p}^{^{\prime} }$ in Equation () varies with depth, typically increasing, which leads to additional variability in G max .…”
Section: Numerical Implementation Of Model Updating Approachmentioning
confidence: 99%
“…The mean value of A was set to 2060, in line with the work conducted by Liu and Zhang 53 . A coefficient of variation (COV) of 0.2 is adopted for A in agreement with the COV values reported by Schevenels et al 57 and Ayad et al, 58 who also modeled G max as a random field. It is important to note that the mean effective normal stress ptrue′ ${p}^{^{\prime} }$ in Equation () varies with depth, typically increasing, which leads to additional variability in G max .…”
Section: Numerical Implementation Of Model Updating Approachmentioning
confidence: 99%
“…For instance, Hamdia et al [46] carried out a sensitivity analysis to determine the key input parameters impacting the relation between tissue structure and mechanics. Ayad et al [47] performed a sensitivity analysis and showed that soil's parameter variability has a significant effect on soil liquefaction probability.…”
Section: Sensitivity Analysismentioning
confidence: 99%